The association of presbyphagia with urinary incontinence and Incontinence-related quality of life in nursing home residents: A cross-sectional study - Ziya Yıldız (PLoS ONE, 2026)
Purpose The association between presbyphagia (age-related swallowing decline) and urinary incontinence (UI) remains poorly understood. This study therefore investigated the relationship between presbyphagia and both UI and incontinence-specific quality of life (I-QOL) in a distinct population of functionally independent healthy elderly in a nursing home. Method The presence of presbyphagia was determined in 73 participants in the nursing home using the 100 ml water swallowing test (100mlSwal) and the Eating Assessment Tool-10 (EAT-10) tests. UI was determined using the International Consultation on Incontinence Questionnaire Short (ICIQ-SF) and I-QOL was determined using the King’s Health Questionnaire (KHQ). The presence of presbyphagia, age and female gender confounding factors were analysed by multiple regression analysis. Multiple linear and binary logistic regression analyses were performed with presbyphagia, age, gender, and handgrip strength. Binary logistic regression was used to calculate odds ratios for UI presence. Results Presbyphagia was significantly associated with UI (p = .001). Individuals with presbyphagia had 7.47-fold higher odds of UI. Presbyphagia was also significantly associated with multiple I-QOL sub-domains, including incontinence impact, role limitation, physical limitation, and emotions (all p < .001). Male gender was associated with higher UI presence (OR=5.16), but not with UI severity. Age showed no significant associations with UI or I-QOL. Conclusion Presbyphagia is independently associated with UI presence and poorer I-QOL in nursing home residents. Male gender was associated with higher UI prevalence but similar severity and I-QOL to females. These findings suggest an independent association between presbyphagia and UI, thereby contributing to the formulation of hypotheses aimed at understanding the complex interactions between oral frailty and the urinary system. Further research is needed to elucidate underlying mechanisms and explore the potential clinical implications of this association. Trial registration ClinicalTrials.gov NCT06827561